2022
DOI: 10.1590/1517-7076-rmat-2022-0111
|View full text |Cite
|
Sign up to set email alerts
|

Duplex treatment on AISI D2 tool steel: plasma nitriding and reactive deposition of TiN and TiAlN films via magnetron sputtering

Abstract: In this work, titanium nitride (TiN) and titanium aluminum nitride (TiAIN) films have been obtained via triode magnetron sputtering. The films were deposited using a direct current source on plasma nitrided AISI D2 tool steel (duplex treatment), non-nitrided steel, and silicon. The nitrided layer was characterized by scanning electron microscopy (SEM), Vickers microhardness, and X-ray diffraction (XRD). The films were characterized by SEM and XRD. The mechanical properties of the coatings were determined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Hence, there is an important need for environmentally friendly cleaning processes. Besides well-studied processes such as plasma nitriding [2], nitrocarburizing [3], and plasma electrolytic oxidation [4], plasma technology has also been studied for cleaning purposes and has shown great potential for development. Some authors worked with oil removal from metal surfaces using plasma [5][6][7][8], and other authors [9,10] showed the importance of plasma cleaning in some industry fields, especially aeronautics.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is an important need for environmentally friendly cleaning processes. Besides well-studied processes such as plasma nitriding [2], nitrocarburizing [3], and plasma electrolytic oxidation [4], plasma technology has also been studied for cleaning purposes and has shown great potential for development. Some authors worked with oil removal from metal surfaces using plasma [5][6][7][8], and other authors [9,10] showed the importance of plasma cleaning in some industry fields, especially aeronautics.…”
Section: Introductionmentioning
confidence: 99%